Analytical, occupational and toxicologic aspects of the degradation products of polypropylene plastics. - Frostling, H.; Hoff, Andreas; Jacobsson, S.; Pfaffli, P.; Vainiotalo, S.; Zitting, Antti (Scandinavian Journal of Work, Environment & Health, 1984)
Thermooxidative degradation of polypropylene (PP) at close to the industrial processing temperatures was studied with thermogravimetric analysis, infrared spectroscopy, and gas chromatography-mass spectrometry (GC-MS). GC-MS allowed identification of 47 volatile degradation products. Formaldehyde, acetaldehyde, alpha-methylacrolein, acetic acid, and acetone were the major products. Antioxidants markedly slowed down the degradation of polypropylene and the evolution of the degradation products. The relative amounts of the oxidized products were mostly independent of the degradation temperature or the type of antioxidant. Measurements in the plastics industry revealed low airborne concentrations of individual volatile products. The concentration of aerosols, which infrared analysis showed to resemble paraffin fumes, was significant and probably the most important hygienic hazard. The biochemical parameters (the consumption of protecting sulfhydryl groups and the effects on foreign compound metabolism) indicated that the degradation products are biologically reactive, affecting the balance of normal metabolism in exposed animals.